ARC Welding Investigation On The Effect Of Independent Input Parameters On Welded Joint Strength Of AISI 1020 Carbon Steel - George Lawai, Galau (Universiti Malaysia Sarawak (UNIMAS), 2018)
Quality and strength of welded joint mainly depends on mechanical and chemical properties of weld metal and heat affected zone in which are directly related to the type of welding and its independent input parameters. The response or output, ultimate tensile strength (UTS), were greatly influenced by welding input parameters amperage or current strength, preheat temperature, and welding time. Images obtained from scanning electron microscope (SEM) also helped in determining the mechanical properties of welded joint such as the existence of voids and the penetration depth of melted welding pool. In this project, type of welding used was shielded metal arc welding (SMAW) and the material used was AISI 1020 Carbon Steel. Response surface methodology (RSM) approach was used as a design of experiment, specifically, using Box-Behnken design technique. Based on experimental results, analysis of variance (ANOVA) was done, mathematical model was developed, graphs and chart were plotted and optimized welding parameters were obtained.